2017
DOI: 10.1007/s00269-017-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

A neutron diffraction study of crystal and low-temperature magnetic structures within the (Na,Li)FeGe2O6 pyroxene-type solid solution series

Abstract: an antiferromagnetic (AFM) coupling within the Fe 3+ O 6 octahedra zig-zag chains and an alternating AFM and ferromagnetic (FM) interaction between the chains, depending on the nature of the tetrahedral GeO 4 chains. The magnetic structure can be described in magnetic space group P a 2 1 /c. Close to the structural phase transition for sample with x(Na) = 0.75, magnetic ordering is observed below 15 K; however, it becomes incommensurately modulated with k = (0.344, 0, 0.063). At 4 K, the magnetic spin structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Only Li can fully exchange for Na as a monovalent cation in the M2 site. Several studies collected diffraction data at temperatures higher or lower than 298 K on synthetic Li-Fe, Li-Cr or LiNi pyroxenes with silicon or germanium in the T site (Behruzi et al 1984, Redhammer et al 2001, 2016, 2017, Camara et al 2009, Tribaudino et al 2009, aiming to understand phase transitions and the magnetic behavior of these phases. Such studies, however, excluded the only naturally occurring Li-pyroxene end member, spodumene (LiAlSi2O6).…”
Section: Lithium Pyroxenementioning
confidence: 99%
“…Only Li can fully exchange for Na as a monovalent cation in the M2 site. Several studies collected diffraction data at temperatures higher or lower than 298 K on synthetic Li-Fe, Li-Cr or LiNi pyroxenes with silicon or germanium in the T site (Behruzi et al 1984, Redhammer et al 2001, 2016, 2017, Camara et al 2009, Tribaudino et al 2009, aiming to understand phase transitions and the magnetic behavior of these phases. Such studies, however, excluded the only naturally occurring Li-pyroxene end member, spodumene (LiAlSi2O6).…”
Section: Lithium Pyroxenementioning
confidence: 99%
“…Finally, Raman spectroscopy showed that some weakly-developed pre-ordering effects were present in the samples, which appeared to be amorphous in PXRD, while well-resolved spectra appeared as soon as the long-range ordered crystalline state could be found with X-ray diffraction.CaFeSi 2 O 6 -aegirine series [4][5][6], diopside CaMgSi 2 O 6 -aegirine series [7][8][9]; the thermal and high pressure behavior [10,11] and the implications of the presence of the aegirine molecule for the behaviour of naturally occurring augitic pyroxenes.In recent years, aegirine has also attracted the attention of numerous physicists due to the observation of multiferroic properties [12], resulting in several studies on its low temperature magnetic properties. In addition, the phase relations and magnetic properties within the (Na,Li)Fe(Si,Ge) 2 O 6 system were investigated with special interest [13][14][15][16][17][18][19][20][21][22][23][24][25]. Aegirine itself shows complex magnetic ordering at low temperatures and discrepancies have been found in the magnetic ground states of naturally-occurring single crystals (with diopsidic and hedenbergitic component dilutions) and synthetic end-member compositions.It was already noted by Ballet and co-workers [26] that phase-pure synthetic NaFeSi 2 O 6 charges are hard to obtain, and that material, produced in ceramic sintering experiments at high temperatures around 900 • C, always contains up to 3-10 wt.…”
mentioning
confidence: 99%
“…In recent years, aegirine has also attracted the attention of numerous physicists due to the observation of multiferroic properties [12], resulting in several studies on its low temperature magnetic properties. In addition, the phase relations and magnetic properties within the (Na,Li)Fe(Si,Ge) 2 O 6 system were investigated with special interest [13][14][15][16][17][18][19][20][21][22][23][24][25]. Aegirine itself shows complex magnetic ordering at low temperatures and discrepancies have been found in the magnetic ground states of naturally-occurring single crystals (with diopsidic and hedenbergitic component dilutions) and synthetic end-member compositions.…”
mentioning
confidence: 99%
“…The differences originate from different pathways for magnetic super-exchange, in turn related to the interaction between structure and magnetic cations. As an example, in (Na,Li)FeGe 2 O 6 pyroxenes [2], commensurate and incommensurate orderings together with spin wave modulations and cycloidal magnetic structure are observed. However, a model relating the crystal structure/composition to magnetic behavior is to our knowledge not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…The abundant literature on the magnetic properties of pyroxenes was mostly devoted to the end members; some studies were performed on the effect of cation exchange of non-magnetic atoms, while keeping fixed the magnetic cation [2,[25][26][27] or between magnetic cations [28,29]. The onset of magnetic behavior introducing a metal in a diamagnetic structure was studied only in (Fe,Mg) 2 Si 2 O 6 clino-and orthopyroxenes, due to their interest as major earth forming minerals [30].…”
Section: Introductionmentioning
confidence: 99%